2009
DOI: 10.1002/ptr.2967
|View full text |Cite
|
Sign up to set email alerts
|

β‐secretase inhibitory effects of furanocoumarins from the root of Angelica dahurica

Abstract: In the course of screening antidementia agents from natural products, five beta-secretase (BACE1) inhibitors were isolated from the root extract of Angelica dahurica (Umbelliferae). They were identified as furanocoumarins, isoimperatorin (1), imperatorin (2), (+)-oxypeucedanin (3), (+)-byakangelicol (4) and (+)-byakangelicin (5). Among them, compounds 2 and 4 showed significant inhibitory activity against beta-secretase (BACE1) with IC(50) values of 91.8 +/- 7.5 and 104.9 +/- 2.4 microM, respectively. Compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…The IMPcontaining herbs are widely used in China for the treatment of osteoporosis and relief of swelling and pain (Zhang et al, 2003). The reported pharmacological activities of IMP include anti-inflammatory properties (Garcia-Argaez et al, 2000), antiosteoporosis (Tang et al, 2008), antibacterial effects (Rosselli et al, 2007), antitumor (Kim et al, 2007), b-secretase inhibition (Marumoto and Miyazawa, 2010), and inhibition of myocardial hypertrophy (Zhang et al, 2010). Recent studies have demonstrated that IMP participates in hypertension treatment by inhibiting voltage-dependent calcium channels and receptor-mediated Ca 2+ influx and release (He et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The IMPcontaining herbs are widely used in China for the treatment of osteoporosis and relief of swelling and pain (Zhang et al, 2003). The reported pharmacological activities of IMP include anti-inflammatory properties (Garcia-Argaez et al, 2000), antiosteoporosis (Tang et al, 2008), antibacterial effects (Rosselli et al, 2007), antitumor (Kim et al, 2007), b-secretase inhibition (Marumoto and Miyazawa, 2010), and inhibition of myocardial hypertrophy (Zhang et al, 2010). Recent studies have demonstrated that IMP participates in hypertension treatment by inhibiting voltage-dependent calcium channels and receptor-mediated Ca 2+ influx and release (He et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…aloeresin D) [29]; isoflavones (bavachinin, neocorylin) and chalcone flavonoids (e.g. bavachromene, bavachalcone) [36]; (+)-vitisinol E, (+)-ampelopsin A, and (+)-vitisin [37]; furanocoumarins (imperatorin, (+)-byakangelicol) [38]; amentoflavone-type biflavonoids (e.g. 2,3-dihydroamentoflavone, 2,3-dihydro-6-methylginkgetin) [39]; resveratrol and its derivatives [40].…”
Section: Discussionmentioning
confidence: 99%
“…β-Secretase inhibitors isolated from A. dahurica roots were types of furanocoumarins (Fig. 3) including isoimperatorin (6), imperatorin (7), (+)-oxypeucedanin (8), (+)-bakangelicol (9) and (+)-byakangelicin (10) (Marumoto and Miyazawa, 2010). Owing to their low molecular weight, these compounds can easily cross the blood-brain-barrier (BBB) and reach the brain.…”
Section: β-Secretase Inhibitorsmentioning
confidence: 99%